2016
DOI: 10.1900/rds.2016.13.79
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal and Gastric Dysmotilities are Associated with Altered Glucose Homeostasis and Plasma Levels of Incretins and Leptin

Abstract: ■ Abstract BACKGROUND:Gastrointestinal complications in diabetes may affect glucose and endocrine homeostasis. Glucosedependent insulinotropic peptide (GIP), glucagon-like peptide-1 (GLP-1), and leptin regulate glucose homeostasis, food intake, and gastric emptying. AIM: The aim was to investigate associations between diabetes complications and glucose homeostasis and plasma levels of GIP, GLP-1, and leptin. METHODS: Sixteen diabetes patients (seven men) were examined with gastric emptying scintigraphy and 72-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This finding is in accordance with the work of Hammersjö et al [9] who showed autonomic neuropathy to be more common in women compared to men. Furthermore, the present results indicated no significant difference in dysphagia according to the type of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the work of Hammersjö et al [9] who showed autonomic neuropathy to be more common in women compared to men. Furthermore, the present results indicated no significant difference in dysphagia according to the type of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
“…Several research teams found a direct relationship between the rate of gastric emptying and postprandial serum glucose levels [ 6 , 7 , 48 , 49 ]. In patients with type 1 diabetes, altered rates of gastric emptying may impair efforts to adjust doses of prandial insulin according to the amounts of ingested nutrients.…”
Section: Glycemic Responses Induced By Fluctuations Of Gastric Empmentioning
confidence: 99%
“…In diabetic patients, gastric emptying may be either accelerated or delayed, with irregular intra- and interindividual fluctuations in the rate and clinical expression [ 4 , 5 ]. Gastric emptying also interacts with overall and postprandial glycemic control [ 6 , 7 ]. Therapeutic approaches aiming to correct both gastric emptying and variations of serum glucose levels include diet changes in meal sequence or content and incretin-based medications [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the MLT receptor has therapeutic potential to treat hypomotility disorders, modulate hunger, and affect glucose metabolism [ 47 ]. The concentrations of GLP-1 [ 48 ] and 5-HT [ 49 ] were lower in diabetes patients with gastroparesis, and exogenous provision of 5-HT reversed delayed gastric emptying. Smiley, Smiley et al reported that the level of SP was significantly decreased in DGP rats [ 50 ].…”
Section: Discussionmentioning
confidence: 99%